The Impact of Entrepreneurial Orientation on Competitive Advantage Moderated by Financing Support in SMEs - Zeebaree, Mohammed R. Yaseen; Siron, Rusinah Bt. (International Review of Management and Marketing, 2017)
The purpose of this study is to examine the relationship between entrepreneurial orientation and competitive advantage and to investigate the moderated role of financial support between the influences of entrepreneurial orientations on competitive advantage. This study adopted a quantitative approach using survey instruments. The targeted sample size was 680 from a total manager population in 3526 SMEs working in Kurdistan Region Government (KRG) in Iraq. The total number of usable questionnaires was 580. Structural Equation Modeling (SEM) was employed to examine the relationship among the variables. The statistical result showed that entrepreneurial orientations significantly influenced on competitive advantage. The results also highlight that financial support had a moderated role in relationship between entrepreneurial orientation and competitive advantage in SMEs in Iraqi Kurdistan Region Government. Keywords: Small and Medium Sized Enterprises, Entrepreneurial Orientation, Financial Support, Competitive Advantage. JEL Classification: L2